حرّية الرأي والتعبير في مصر وفرنسا : دراسة تطبيقية مقارنة بالشريعة الإسلامية - محمد علي ، محمد محمد عباس (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
This research aims to highlight that the right to freedom of opinion and expression is inherent to the human being and is the cornerstone of other rights and freedoms. It purposes to show the position of Islamic law and its precedent in recognizing and protecting this right over other conventional laws. As well as to identify the deficiencies in the French and Egyptian laws in the field of codification of the right to freedom of opinion and expression. However, the problematic statement of this research tends to address is whether the applications of the right to freedom of opinion and expression in French and Egyptian law are compatible with their legal theories. Or is there a contradiction and duplication of standards at the applied level? What is the extent of the theorization and application of the two laws with Islamic law? This is done through the use of the inductive method: to extrapolate laws relating to freedom of opinion and expression, as well as the provisions of Islamic law and opinions of jurists in the same subject. Comparative approach is used to highlight the similarities and differences between the laws of Egypt, France and Islamic law in establishing and exercising the right to freedom of opinion and expression. This study reached several conclusions, the most important of which are: Islam is the pioneer in introducing the concepts of freedoms and human rights and guarantee them before Western civilization and the world knew these concepts. It is found that French law included contradictions and duplication in the application of freedom of opinion and expression. Especially the right of freedom of belief, practice of religion and freedom of information with Muslims, as well as Egyptian law with opponents of the regime specifically. The researcher recommended several recommendations, the most important of which are: Calling on the current secularists in the Islamic countries in general and in Egypt in particular to look impartially and scientifically to the freedom of opinion and expression in Islamic law and compare it with all the existing old and new laws. Intellectuals, jurists, scholars and elders of Islam must clarify the greatness of Islam in the freedom of opinion and expression in a simple and clear way by all means available to them. Inviting scholars and thinkers of the Islamic Ummah to contribute to the intellectual awareness of the community through submitting projects and proposals calling for adherence to the controls of freedom of expression in Islam. Finally, to create a parallel media to the current media, adopting the principles and objectives of the Islamic media.